Identified Determinants of the Conceptual HRM Framework - Andalib, Tarnima Warda; Mohd Ridzuan, Darun (Universiti Malaysia Pahang, 2016)
Employees have certain roles to play in an organization as well as they have certain rights from the organization. To blend these two is indeed a significant challenge for any organization and its leaders. In this paper, the determinants of that significant framework has been discussed which are found through some in-depth interviews with some of the practitioners of the real world.